Spirituality for sale in the era of globalisation - Abdul Razak, Mohd Abbas; Machouche, Salah (Department of Communication, AHAS-Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), 2022)
At times, modernity and its complexities can drive people in the modern world into madness. Despite the fact that people in the urban areas are surrounded by the gifts of science and technology, there are moments in their lives, when they might think and feel that all electronic gadgets which keep their life going, become meaningless. Under certain circumstances in life, regardless of whether people live in the modern setting in the urban or in the remote areas, they go through similar human experiences. Though the outer world of the two can somehow be different due to economic disparities, their inner world and the dynamics at work are pretty much the same. As human beings, at some point in their lives, both are bound to go through psychological burdens like stress, anxiety, anger, depression, bereavement, etc. When there is something boiling and bubbling in the inner world, meaning to say in the deep recesses of their hearts, people wherever they are, look for a quick fix to solve their problems. During such desperate situations, people seek some sort of divine intervention, a philosophy or a mind-control technique to get themselves out of their awful and pathetic condition. Since most people do know the ways and methods how to calm down their hearts, minds and souls, they seek help from those who are experts.